High friction moments in large hard‐on‐hard hip replacement bearings in conditions of poor lubrication. Issue 5 (13th December 2012) - Bishop, Nicholas E.; Hothan, Arne; Morlock, Michael M.
Abstract Disappointing clinical results for large diameter metal replacement bearings for the hip are related to compromised lubrication due to poor cup placement, which increases wear as well as friction moments. The latter can cause overload of the implant–bone interfaces and the taper junction between head and stem. We investigated the influence of lubrication conditions on friction moments in modern hip bearings. Friction moments for large diameter metal and ceramic bearings were measured in a hip simulator with cup angles varying from 0° to 60°. Two diameters were tested for each bearing material, and measurements were made in serum and in dry conditions, representing severely compromised lubrication. Moments were lower for the ceramic bearings than for the metal bearings in lubricated conditions, but approached those for metal bearings at high cup inclination. In dry conditions, friction moments increased twofold to 12 Nm for metal bearings. For ceramic bearings, the increase was more than fivefold to over 25 Nm. Although large diameter ceramic bearings demonstrate an improvement in friction characteristics in the lubricated condition, they could potentially replicate problems currently experienced due to high friction moments in metal bearings once lubrication is compromised. © 2012 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 31: 807–813, 2013